Analysis of muscle fiber conduction velocity during finger flexion and extension after stroke. Issue 4 (19th May 2017) - Conrad, Megan O.; Qiu, Dan; Hoffmann, Gilles; Zhou, Ping; Kamper, Derek G.
Abstract: Background: Stroke survivors experience greater strength deficits during finger extension than finger flexion. Prior research indicates relatively little observed weakness is directly attributable to muscle atrophy. Changes in other muscle properties, however, may contribute to strength deficits. Objectives: This study measured muscle fiber conduction velocity (MFCV) in a finger flexor and extensor muscle to infer changes in muscle fiber-type after stroke. Methods: Conduction velocity was measured using a linear EMG surface electrode array for both extensor digitorum communis and flexor digitorum superficialis in 12 stroke survivors with chronic hand hemiparesis and five control subjects. Measurements were made in both hands for all subjects. Stroke survivors had either severe ( n = 5) or moderate ( n = 7) hand impairment. Results: Absolute MFCV was significantly lower in the paretic hand of severely impaired stroke patients compared to moderately impaired patients and healthy control subjects. The relative MFCV between the two hands, however, was quite similar for flexor muscles across all subjects and for extensor muscles for the neurologically intact control subjects. However, MFCV for finger extensors was smaller in the paretic as compared to the nonparetic hand for both groups of stroke survivors. Conclusions: One explanation for reduced MFCV may be a type-II to type-I muscle fiber, especially in extrinsic extensors. Clinically, therapists may use this information to develop therapeutic exercises targeting loss of type-II fiber in extensor muscles.